An important role of coal and its calorific value on the performance of thermal power station: A case study - Pardhi, Om Prakash; Sahu, Bed Lal; Upadhyay, Manish; Dwivedi, Pratima Rani; Augur, M R; Pandey, Rajiv Ratna; Pathak, Krishna Kumar (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> An investigation was undertaken to study the Physical and Chemical properties of coal in Korba district. Due to the Presence of lot of Coal mines, number of coal based thermal power stations are established in Korba district. So study has been carried out for assessment of coal quality, whether it is suitable for thermal power stations, by collectying sample from Gevra Coal mines. This paper presents Grade of the coal available in Korba district. Three different Coal samples were collected from different areas of Gevra Coal mines and analyzed for Proximate, Ultimate and Calorific value as per Standard methods. The useful heat values (UHV) of three coal samples are 2482K.Cal/Kg, 2917K.Cal/Kg, and 2786K.Cal/Kg. From overall analysis, and according to UHV of coal samples we can conclude that the grade of Gevra Coal is” F”and is very much useful for Coal based thermal power stations. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>